Surface microstructures and properties of thiol-epoxy/thiol-Si-methacrylate hybrid polymer networks prepared by UV-induced polymerization. Issue 5 (3rd May 2020) - Xin, Fuhua; Han, Junyi; Pan, He; Sun, Fang
Abstract: The thiol-epoxy/thiol-Si-methacrylate (namely polysiloxane-methacrylate) hybrid networks with systematic variations were prepared by free-radical photoinitiator (ITX) and photo-base generator (TBD·HBPh4 ) that induce photopolymerization. The photopolymerization kinetics investigated with real-time infrared spectroscopy indicated that the thiol-Si-methacrylate reaction was faster and more efficient than the thiol-epoxy reaction (>80% conversion in about 60 seconds and 7–10 min, respectively), and the thiol conversion increased with an increase of the Si-methacrylate content. The effect of the Si-methacrylate content on the microtopography and properties of the UV-cured films was systematically studied. The results showed that the introduction of Si-methacrylate into the hybrid systems can enhance the thermostability and elongation at break of the films, and reduce glass-transition temperature (Tg ), hardness and tensile strength. Moreover, the increase of the polysiloxane-methacrylate content in the hybrid networks can reduce the dispersion surface energy of the polymer films to generate a more hydrophobic surface. Graphical Abstract: